Consumers' Experiences in Dual Focus Mutual Aid for Co-occurring Substance Use and Mental Health Disorders. (January 2013) - Matusow, Harlan; Guarino, Honoria; Rosenblum, Andrew; Vogel, Howard; Uttaro, Thomas; Khabir, Sadiqua; Rini, Martin; Moore, Thomas; Magura, Stephen
Mutual aid fellowships have been shown to improve outcomes for those with co-occurring substance use and mental illness disorders. Processes associated with usefulness include helper therapy (the assumption of a helping role to foster commitment) and reciprocal learning (the sharing of problems and solutions among members). The present qualitative investigation used focus groups comprised a subset of participants in Double Trouble in Recovery (DTR), a 12-step mutual aid group for those with co-occurring disorders, to gather their subjective perceptions of the groups. Participants emphasized that in linking them to others with similar problems, the DTR groups played a vital emotional role in their lives and provided a needed venue for information sharing that might have been otherwise unavailable.